Winning wars amongst the people case studies in asymmetric conflict - Kiss, Peter A. (Potomac Books, an imprint of the University of Nebraska Press, 2014)
Since the end of World War II a paradigm shift has occurred in armed conflict. Asymmetric, or fourth-generation warfare-the challenge of nonstate belligerents to the authority and power of the state-has become the dominant form of conflict, while interstate conventional war has become an increasingly irrelevant instrument of statecraft. In asymmetric conflicts the enemy is often a fellow citizen with a different vision for the future of the country-waging war among the people, maneuvering on the borderlines between parliamentary politics, street politics, criminal activity, and combat operations.